Perwatakan Tokoh Utama dalam Novel Egosentris Karya Syahid Muhammad - Septia Esramelda; Hasanuddin WS (Lembaga Yasin AlSys, 2026)
Although studies on character traits in literary works continue to develop, analyses that specifically emphasize sociological aspects through an objective approach are still relatively limited. This study aims to describe the characterization of the main character in the novel Egosentris by Syahid Muhammad based on sociological aspects. This study employed a qualitative approach with a descriptive design. Data in the form of words, phrases, clauses, and sentences related to the character’s social background were collected through intensive reading and note-taking techniques, then analyzed using thematic analysis through the stages of identification, classification, and interpretation. The results showed that the characterization of the main character was shaped by sociological aspects including social status, education, occupation, and hobbies. The character’s social status within the lower-middle economic stratum gave rise to social pressure and injustice that influenced his attitudes and behavior. The educational aspect indicated the presence of academic pressure that also shaped the character’s mindset, while occupation reflected the character’s social responsibility and independence in dealing with economic limitations. Meanwhile, hobbies functioned as a way for the character to respond to the social pressures he experienced. These findings affirm that the social environment has an important role in shaping character traits in literary works. This study contributes to strengthening characterization studies and can be utilized in literature learning.